Investigations on the structural and optoelectronic characteristics of cadmium-substituted zinc selenide semiconductors - Iqbal, Muhammad Aamir; Bakhsh, Sunila; Ikram, Mujtaba; Sohail, Muhammad; Islam, Md. Rasidul; Manoharadas, Salim; Choi, Jeong Ryeol (Frontiers in Chemistry, 2023)
A change in the composition and dopant content of selective atoms in a material leads to their new desired properties by altering the structure, which can significantly improve the performance of relevant devices. By acknowledging this, we focused on characterizing the optoelectronic and structural properties of cadmium-substituted zinc selenide (Zn1-xCdxSe; 0 ≤ X ≤ 1) semiconductors using density functional theory (DFT) within the generalized gradient approximation (GGA), EV-GGA, and mBJ approximations. The results proved the cubic symmetry of the investigated materials at all Cd concentrations (0, 0.25, 0.50, 0.75, and 1). Although a linear surge in the lattice constant is observed with the change in Cd content, the bulk modulus exhibits a reverse trend. These materials are observed to be direct bandgap semiconductors at all Cd concentrations, with a decrease in electronic bandgap from 2.76 eV to 1.87 eV, and have isotropic optical properties, showing their potential applicability as a blue-to-red display. The fundamental optical properties of the materials, such as optical conductivity, reflectance, refractive index, absorption, and extinction coefficient, are also discussed. These outcomes provide a computational understanding of the diverse applications of Zn1-xCdxSe semiconductors in optoelectronic, photonic, and photovoltaic devices, particularly for a visible-range display.